إدارة أموال القاصرين واستثمارها في إقليم كوردستان العراق : دراسة تقويمية في ضوء الفقه الإسلامي - برايم، زبير يونس (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2013)
All heavenly religions and secular laws pay attention to the weak and orphans and the like, in particular the Islamic law, which commands us to protect the wealth of those under guardianship and invest it until they reach majority and their maturity is sensed. The Iraqi Minors' Welfare Act No. (٧٨) for ١٩٨٠, enforced in the Kurdistan Regional Government of Iraq shows interest in the minors' well-being and stipulates the punishment of those who abuse their rights or wealth. This research focuses on understanding how the funds of the vulnerable and orphans in the Kurdistan region of Iraq are invested and the extent of their government's attention. Their investment is also compared to other countries. The researcher has adopted the inductive approach to investigate how their funds are being invested, drawing on field visits to the relevant departments of minors as well as interviews with some staff. The researcher concluded that the Government of the region, although showing interest in minors and their wealth, has stopped investing their money. The researcher then chose two of the safest means of investment to preserve their wealth which are exchanging the minors' riches with gold instead of currency and investing or exchanging their cash and “transportable possessings” with properties and estates, hoping that the regional Directorates of Minors' Welfare would use those ways to protect the minors' wealth from extinction or loss, especially during political and economic crises and the rapid decline of the currency in circulation in the country. The researcher also mentioned in the last chapter, that the law considers a minor who is ١٥ years old a person with full capacity in the case of marriage with the permission of the Court, and this is unique to this law; however, it violates all regulations and ordinances in this regard, and has dire consequences. The researcher stated that the training of a minor to manage his funds and invest them is the duty of parents and guardians before handing them over to him; however, the law in the region does not establish training courses for minors, and also does not force parents and guardians to train minors to manage their money before they reach the legal age of majority; this matter is left to the minors when they reach the legal age of ١٨ but this could also have devastating consequences.